Asef controls vascular endothelial permeability and barrier recovery in the lung - Tian, Xinyong (Mol Biol Cell, 2015)
Increased levels of hepatocyte growth factor (HGF) in injured lungs may reflect a compensatory response to diminish acute lung injury (ALI). HGF-induced activation of Rac1 GTPase stimulates endothelial barrier protective mechanisms. This study tested the involvement of Rac-specific guanine nucleotide exchange factor Asef in HGF-induced endothelial cell (EC) cytoskeletal dynamics and barrier protection in vitro and in a two-hit model of ALI. HGF induced membrane translocation of Asef and stimulated Asef Rac1-specific nucleotide exchange activity. Expression of constitutively activated Asef mutant mimicked HGF-induced peripheral actin cytoskeleton enhancement. In contrast, siRNA-induced Asef knockdown or expression of dominant-negative Asef attenuated HGF-induced Rac1 activation evaluated by Rac-GTP pull down and FRET assay with Rac1 biosensor. Molecular inhibition of Asef attenuated HGF-induced peripheral accumulation of cortactin, formation of lamellipodia-like structures, and enhancement of VE-cadherin adherens junctions and compromised HGF-protective effect against thrombin-induced RhoA GTPase activation, Rho-dependent cytoskeleton remodeling, and EC permeability. Intravenous HGF injection attenuated lung inflammation and vascular leak in the two-hit model of ALI induced by excessive mechanical ventilation and thrombin signaling peptide TRAP6. This effect was lost in Asef(−/−) mice. This study shows for the first time the role of Asef in HGF-mediated protection against endothelial hyperpermeability and lung injury.